The evaluation of right ventricle dyssynchrony by speckle tracking echocardiography in systemic sclerosis patients. Issue 9 (14th July 2021) - Demirci, Murat; Ozben, Beste; Sunbul, Murat; Cincin, Altug; Gurel, Yusuf Emre; Bayram Guctekin, Tuba; Dogan, Zekeriya; Sahinkaya, Yasemin; Direskeneli, Haner; Tigen, Kursat; Sayar, Nurten
Abstract: Purpose: Systemic sclerosis (SSc) is associated with right ventricle (RV) remodeling and dysfunction. The primary aim of this study was to evaluate RV dyssynchrony (RV‐Dys) in SSc patients using two‐dimensional speckle tracking echocardiography (2D‐STE). Methods: Fifty‐five SSc patients with functional class I‐II and 45 healthy controls were consecutively included and underwent 2D‐STE. RV‐Dys was defined as the standard deviation of time to peak strain of mid and basal segments of RV free wall and interventricular septum. SSc group was further classified according to the presence of pulmonary arterial hypertension (PAH). Patients with tricuspid regurgitant velocity >2.8 m/s with additional echocardiographic PAH signs were defined as SSc PAH (+). Results: SSc patients had lower RV longitudinal strain (RV‐LS) (−17.6 ± 4.6% vs. −20.8 ± 2.8%, p  < 0.001) and greater RV‐Dys (49.9 ± 25.4 ms vs 24.3 ± 11.8 ms, p  = 0.006) than controls despite no significant difference in conventional echocardiographic variables regarding RV function. Although SSc PAH(+) patients had lower RV‐LS and higher RV‐Dys than SSc PAH(−) patients, the differences were not statistically significant. The only independent predictor of RV‐Dys was RV‐LS (β:‐0.324 [−3.89– −0.45]; p  = 0.014). Conclusion: SSc patients had not only reduced RV‐LS but also impaired RV synchronicity even as conventional echocardiographic variables were preserved.